Nitrogen removal capacity and influencing factors of inland wetland under human activities: Jiashan County, China - Niu Li; Youzheng Zhang; Jinlong Wu; Junzhen Li; Jingwen Gao; Pengcheng Jiang; Xiaoqi Ye; Ming Wu (River)
Abstract Inland wetlands play a vital role in mitigating non‐point source nitrogen loads through denitrification and anammox processes. However, the impact of varying human activities within the same region on these nitrogen removal processes of inland wetlands remains unclear. This study investigated the differences in nitrogen removal rates of wetland sediments under various human activities in Jiashan County, China. 15N isotope tracing was used to determine denitrification and anammox rates. Denitrification was the primary nitrogen removal pathway, with an average contribution of 82.34%. Denitrification and anammox rates varied significantly under different human influences, with the highest rates in residential and agricultural areas. NH4+, chlorophyll a, NO3−, and pH were the main environmental factors. This study highlights the need for targeted wetland management and restoration strategies based on the type and intensity of human activities. Protecting and restoring these “natural purifiers” is crucial for improving regional water quality and maintaining the ecological functions of wetlands in rapidly urbanizing landscapes.